The Effectiveness of New Student Admission Promotion at Institut Hindu Dharma Negeri Denpasar - Sudarsana, I Ketut; Alit Widyawati, Anak Agung Ayu (Jayapangus Press, 2020)
This study aimed to analyze the effectiveness of new student admission promotion at Institut Hindu Dharma Negeri Denpasar. The analysis results were used to control and develop new student admission policies in the following year to increase the number and quality of new students. This study was a survey research, where the subjects were prospective new students who registered at IHDN Denpasar in 2020. Reviewed aspects to determine the effectiveness of new student admission socializations were based on indicators according to Kotler’s opinion, which states that the promotion mix consists of five main tools: advertising, sales promotion, public relations and publicity, personal selling, and direct marketing. The results showed that the school status of prospective new students obtained 73.1% of IHDN Denpasar prospective new students who came from public schools. 63.5% of IHDN Denpasar prospective new students prefer the Faculty of Dharma Acarya. The desire level to choose IHDN Denpasar showed that 466 people (97.1%) decided to study at IHDN Denpasar of their own accord. 149 people (31%) of prospective new students received information about IHDN Denpasar from their families. IHDN Denpasar prospective new students get more information about IHDN Denpasar through the Instagram of 229 people (47.7%). 386 people (80.4%) of IHDN Denpasar prospective new students have never participated in the socialization of the IHDN Denpasar New Student Admissions Committee at school. 331 people (69%) stated that they had never attended or watched IHDN Denpasar arts activities/performances.